The Effect of Relocating Street Hawkers on Urban Vitality in the Malioboro Tourism Area, Yogyakarta - Eva Sanchia Janita; Woerjantari Kartidjo (Jurnal Sosioteknologi, 2023)
Since the 1970s, street hawkers have considered Malioboro an icon of the city of Yogyakarta. Malioboro has become increasingly crowded. Seeing this condition, a decision was made to relocate the street hawkers from the Malioboro corridor. This decision has pros and cons; some consider street hawkers to be a place for creativity, a sector that greatly affects the level of crowds and is the main attraction for the Malioboro area. However, few people consider it a barrier to the original face of the Malioboro corridor. Urban vitality is an important aspect of increasing visitor interest; it relates to comfort, security, safety, and fun as the main indicators. This study aims to examine the impact of the relocation decision on the vitality of Malioboro as a tourist area. Using qualitative methods, this study compared the reality through field surveys and online questionnaires that had been distributed for one week to a total of 61 respondents who had ever visited Malioboro with the theory of urban vitality and urban tourism precincts. To get a conclusion on whether the Yogyakarta city government’s decision to relocate the street hawkers from Malioboro Street can maintain or even reduce Malioboro’s urban vitality.